Convolution coder software implementation using VIiterbiDecoding algorithm - Khalifa, Othman Omran; Al-Maznaee, Tariq; Munjid, Mahmood; Hussan, Aisha (2008)
This In this paper, Convolutional coder software implementation using Viterbi decoding algorithm for bitstream that has been encoded using Forward error correction is presented. It will discuss the detailed description and the steps involved in simulating a communication channel using convolutional encoding with Viterbi decoding. The steps will involve generating random binary data, convolutionally encoding the data, passing the encoded data through a noisy channel, quantizing the received channel symbols, and finally performing Viterbi decoding on the quantized channel symbols to recover the original binary data. The paper will be in a convincing manner and authors aim to explain to the reader the advantages of convolutional coding with Viterbi decoding over conventional decoding techniques in terms of BER.